Cell type-specific regulation of CFTR trafficking—on the verge of progress - Farinha, Carlos M.; Santos, Lúcia; Ferreira, João F. (Frontiers in Cell and Developmental Biology, 2024)
protein is a complex process that starts with its biosynthesis and folding in the endoplasmic reticulum. Exit from the endoplasmic reticulum (ER) is coupled with the acquisition of a compact structure that can be processed and traffic through the secretory pathway. Once reaching its final destination -the plasma membrane, CFTR stability is regulated through interaction with multiple protein partners that are involved in its post-translation modification, connecting the channel to several signaling pathways. The complexity of the process is further boosted when analyzed in the context of the airway epithelium. Recent advances have characterized in detail the different cell types that compose the surface epithelium and shifted the paradigm on which cells express CFTR and on their individual and combined contribution to the total expression (and function) of this chloride/bicarbonate channel. Here we review CFTR trafficking and its relationship with the knowledge on the different cell types of the airway epithelia. We explore the crosstalk between these two areas and discuss what is still to be clarified and how this can be used to develop more targeted therapies for CF.